Human health in peril: The need to upgrade medical education in light of COVID-19 - Gatterer, Lukas; Kriwan, Fabian; Tanous, Derrick; Wirnitzer, Katharina (Frontiers in Medicine, 2022)
While we might leave the COVID-19 pandemic behind, future health professionals are still confronted with another global phenomenon: the increasing pandemic of non-communicable diseases (NCDs). Both issues are strongly interwoven, yet current medical education fails to address their syndemic nature accordingly. There is scientific consensus that (i) most emerging infectious diseases are zoonotic, (ii) the overexploitation of earth's resources for animal protein production (i.e., tropical deforestation) rapidly escalates human contact with unknown pathogens, and (iii) people following a healthy plant-based diet present fewer rates of NCDs as well as severe illness and mortality from COVID-19. A shift toward whole food plant-based nutrition in the general population thus holds the potential to tackle both public health threats. We are convinced that it is every physician's responsibility to care for individual, public, and global health issues; however, future health professionals are not trained and educated regarding the health potential of plants and plant-based diets. The COVID-19 pandemic has demonstrated the urgent need for a “prevention first” approach. Therefore, in order to upgrade medical education worldwide and protect current and future human health properly, greater medical professional awareness of evidence on plant-based diets is urgently needed in classes, universities, and hospitals.